스피드 팩토리 로봇카페 서비스 개발의 전략적 요인에 관한 연구: 무인화 단계에 따른 평가 - 김태진; 강주영 (경영학연구, 2021)
Depending on the unmanned level, this study derives the strategic factors for developing robot cafe services which are increasing significantly because of a combination of digital transformation and the COVID-19 pandemic. As a frame that combines UTAUT and SERVQUAL, and as a result of conducting the Delphi method through industry experts, the 8 top factors have been identified as performance expectancy, social influence, facilitating conditions, trust, ease of use, pleasure, satisfaction, and environmental factors. The18 sub-factors derived are utilization performance, untact, legal regulations, finances, technology, management environment organization, safety design, role responsibility, service stability, service safety, education manual, convenience, efficiency, pleasure by robots, emotions, quality, personalization, and environmental design factors. This study will present a wealth of practical implications to the entrepreneurs and corporate managers who start robot cafes on how to survive digital Darwinism brought about by digital transformation.
Keywords: Robot Café; Smart Factory; Cooperative Robot; Unmanned; Untact; Delphi; Speed Factory